Menelisik Munculnya Perilaku Hijau Karyawan Melalui Budaya Hijau Organisasi dan Komitmen Organisasi - Putri, Naila Cahayani; Fajrianthi (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
Research on employee green behavior is increasing as companies are becoming more aware of environmental protection. The implementation of green culture is thought to help organizations in shaping green behavior among employees, but past researches show inconsistency regarding the significant impact of green organizational culture on employee green behavior. To bridge this gap, this study investigates the impact of green organizational culture on employee green behavior through organizational commitment. Data was obtained from questionnaires filled out by 111 employees from companies that have acquired ISO 14001 certification. This research employs model 4 PROCESS macro by Andrew F. Hayes available in SPSS 26 for Windows. The result shows that green organization culture significantly and positively affects employee green behavior and organizational commitment. Contrary to the expectation, this research found that organizational commitment does not mediate the positive impact of green organizational culture on employee green behavior.